Knowledge, attitudes and practices of health professionals in management of pain in aids patients at Polokwane/ Mankweng Hospital complex, Limpopo Province - Ratshikana-Moloko, Mja (Department of Public Health and Family Medicine, 2014)
Includes bibliographical references.